Antibody structure and function: antibody function - Clark, Mike (Henry Stewart Talks, 2021)
The significance of valency in antigen recognition, Functional properties of antibodies, The role of different classes and subclasses of antibodies in immune functions, Immune complexes, Fc Receptors, Allotypes